A model to understand risk behavior: Interoception awareness and motivational systems in the binge watching. - Giuseppe Forte; Francesca Favieri; Francesca Agostini; Maria Casagrande; Renata Tambelli (Heliyon)
This study aims to test the interoceptive-motivational hypothesis as a possible marker for the risk of developing binge-watching (BW) as a behavioral addiction. Like other risky behaviors, BW can be included in a model that includes the interaction of personological and physiological factors as predictors of the behavioral outcome. On a sample of 741 young adults, a structural equation model considered the association between the interoceptive indices (MAIA questionnaire), inhibition/activation systems (BIS/BAS questionnaire) of the motivational theory, and BW pattern (BWAQ questionnaire). The results suggested a different interaction between the variables when BW was considered as a leisure activity and as an at-risk behavior. While in the first case, interoception and BIS/BAS systems interact, and BIS and interoception positively affect the increase of BW as a leisure activity, in BW as at-risk behavior, the interoceptive-motivational link is lost, and a different pattern of association with the behavior emerges. BIS and BW are still positively associated with the problematic expression of the behavior. The result would suggest that persons exhibiting better interoceptive sensitivity display lower risk of addictive BW. Finally, the interoceptive-motivational model, if confirmed in other at-risk behaviors, would provide a new perspective in the field of behavioral addictions.